2020
DOI: 10.1183/23120541.00196-2020
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with antifibrotic agents in idiopathic pleuroparenchymal fibroelastosis with usual interstitial pneumonia

Abstract: BackgroundThere are no established therapeutic options available for idiopathic pleuroparenchymal fibroelastosis (IPPFE), apart from supportive care and lung transplantation. Furthermore, it is known that IPPFE with a usual interstitial pneumonia (UIP) pattern and lower lobe predominance is a disease entity distinct from idiopathic pulmonary fibrosis (IPF). To our knowledge, few studies are available that report on the efficacy of antifibrotic agents for IPPFE with UIP.AimThe aim of this study was to compare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Conventional drugs mainly include prednisone+azathioprine+acetylcysteine which can inhibit the inflammatory reaction, dissolve and promote the expectoration of sputum. 13,14 Based on the comprehensive assessment of the patient's condition, pulmonary rehabilitation therapy may additionally provide protein supplementation, oxygen inhalation, exercise and respiratory training guidance and psychological intervention. Protein supplementation can promote the improvement of immune function, while oxygen inhalation can improve the symptoms of dyspnea.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional drugs mainly include prednisone+azathioprine+acetylcysteine which can inhibit the inflammatory reaction, dissolve and promote the expectoration of sputum. 13,14 Based on the comprehensive assessment of the patient's condition, pulmonary rehabilitation therapy may additionally provide protein supplementation, oxygen inhalation, exercise and respiratory training guidance and psychological intervention. Protein supplementation can promote the improvement of immune function, while oxygen inhalation can improve the symptoms of dyspnea.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of the drug is negligible because the use of nintedanib for progressive fibrosing ILD was started in Japan in 2020. In addition, a retrospective study showed that the efficacy of antifibrotic agents was limited in PPFE patients with UIP [ 42 ]. Third, we have recently reported that high serum LTBP-4 levels may be associated with a poor prognosis in PPFE patients [ 22 ]; however, serum LTBP-4 was not measured in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Patients often receive low-dose glucocorticoids, however, immunosuppressive therapy is generally discouraged [54]. The antifibrotic agents pirfenidone (not approved for this indication) [7 ▪ ,12 ▪ ,21,71] and nintedanib [44 ▪▪ ] have been used is few cases, and interpretation of data is often confounded by the association of PPFE and UIP patterns [24]. In the INBUILD study of nintedanib in patients with ILD and a progressive fibrosing phenotype (progressive pulmonary fibrosis) [72], a low number of patients with PPFE were enrolled [73].…”
Section: Drug Therapymentioning
confidence: 99%